Race Across America - Stilton, Gernimo (New York Scholastic Inc., 2024)
Geronimo Stilton is out on another adventure and in this one, he is ready with his cycling gear. The mouse detective is the editor and founder of The Rodent's Gazette, where he prints his latest adventures. Living in New Mouse City along with his sister Thea, cousin Trap and nephew Benjamin, Stilton is a quiet soul preferring to spend his time reading or collecting cheese rinds, instead of socializing or venturing out into the unknown. The Race Across America: 37 (Geronimo Stilton) starts off by Geronimo receiving anonymous gifts in the mail, which turn out to be separate parts of a bicycle. Confused by the packages he is getting, Stilton finally discovers the source and is surprised to find his friend Bruce Hyena at his doorstep. As unbelievable as it sounds to him, he discovers that his friend has signed him up for a race across America no less. Geronimo Stilton races across an entire nation in this new and entertaining installment of the Geronimo Stilton series. The Race Across America: 37 (Geronimo Stilton) was published by Scholastic Incorporated in 2009 and is available in paperback. Key Features: Beautifully laid out text with corresponding colorful images, makes this book a hit with children.
Keywords: Fiction